THE CRYPTOCURRENCY MARKET: THE DEVELOPMENT FORECAST - V. Shaydullina (Вестник университета, 2018)
This article presents the analyze of the cryptocurrency market, the practice of state regulation of the cryptocurrency. During the market research of the cryptocurrency and the experience of its regulation, author identified certain similarities. First, each state strives to create a favorable climate for the development of new technologies (blockchain), seeing a great potential for using technology in the public and private sectors. Secondly, there is a rapid growth of the cryptocurrency market, and the state, not adapting the existing national legislation to the existing challenges of the digital economy, faces a lack of revenue to the budget, since the cryptocurrency is outside the legal jurisdiction. Third, today there are over a thousand different cryptocurrencies, accordingly, unified standards for their regulation should be developed.